(untitled) (Journal of Parents and Teachers, 2024)
Brunhilda is a creature who lives in the depths of the sea with her father, the scientist and sorcerer Fujimoto, and her sisters. One day, taking advantage of an oversight by her father while he watches the comings and goings of fish, squid and jellyfish, Brunilda leaves her home, curious about what the surface has to offer. There she meets Sōsuke, a five-year-old boy who lives with his mother, Lisa, and who rescues her adrift, trapped in a glass bottle, after having almost fallen into the nets of a fishing boat. Sōsuke takes care of her and feeds her, renaming her Ponyo and launching a strong friendship between the two. But their relationship generates a profound imbalance between sea and land, as well as an inevitable clash between the protective desires of Ponyo’s father and the girl’s desire to be reunited with her new friend, even at the cost of becoming human to be with him, on dry land.